LEATHER QUALITY ASSESSMENTS OF ANTELOPE AND WEST AFRICAN DWARF GOAT - Elaigwu, S. O.; Kalla, D. J. U.; Egbo, M.L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study investigates the physical leather quality characteristics of West African Dwarf goat and antelope leather skin based on the tanning methods (vegetable and chemical) and position of the leather (butt, shoulder and belly). The carved skin was gotten from live animals been sourced from the market and was sundried after flaying. The slaughtering of the animals followed ethical standard. The skins were stored, shared into two separate parts and tagged with number prior to tanning. After tanning, samples from the butt, shoulder and belly were taken to determine the shrinkage temperature, water vapor, weight, thickness, mass, density, resistance to compression, indentation index, hardness, maximum force/kg and displacement properties. The main effect for the species indicates that there was no effect for all the properties except for thickness and density (1.94±0.45) at (P <0.01), while for tanning method there were significant difference at (P<0.01) for shrinkage (81.67±12.18), temperature, water vapor (1125±534.10) and density against the other properties. Also, the position had significant difference in hardness, maximum force, mass and density, while the others had no effect. For the interaction effect, for position and specie on weight and in specie and tanning on mass had effects, while all other had no significant difference. However, this study reveals that goat and antelope leather can be used side by side for industrial production and vegetable tanning which is cheap, safe, environmentally friendly should be considered. Therefore, the position stipulates the kind of finished leather product to be desired. Essentially, the shoulder and butt position would be utilized for hard leather works while the belly for soft products.